Control of three-phase PWM boost rectifiers using proportional-resonant controllers - Rocha, Marco Auralio [UNESP] (2018)
Voltage-oriented vector control (VOC) using proportional-integral controllers is an attractive control method for three-phase PWM rectifiers, due to relative ease of implementation, being one of the most used methods. However, these controllers present oscillatory DC voltage for unbalanced input voltage and harmonics in the current due to the AC-DC converter switching. Thus, this work presents a control strategy for three-phase driven by sinusoidal PWM in the stationary reference frame using proportional-resonant controllers in the internal current loop. This control strategy presents high dynamic performance, simplicity of implementation, attenuation of harmonics generated by converter switching, reduction of ripple at link-DC voltage and less dependence on physical parameters, since the decoupling term is eliminated. Simulation results show an excellent performance of the proposed method with a ripple reduction of DC-link voltage, THD reduction of the grid current, fast transient response for power variations.